If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x(3x + -4) = 180 Reorder the terms: x(-4 + 3x) = 180 (-4 * x + 3x * x) = 180 (-4x + 3x2) = 180 Solving -4x + 3x2 = 180 Solving for variable 'x'. Reorder the terms: -180 + -4x + 3x2 = 180 + -180 Combine like terms: 180 + -180 = 0 -180 + -4x + 3x2 = 0 Begin completing the square. Divide all terms by 3 the coefficient of the squared term: Divide each side by '3'. -60 + -1.333333333x + x2 = 0 Move the constant term to the right: Add '60' to each side of the equation. -60 + -1.333333333x + 60 + x2 = 0 + 60 Reorder the terms: -60 + 60 + -1.333333333x + x2 = 0 + 60 Combine like terms: -60 + 60 = 0 0 + -1.333333333x + x2 = 0 + 60 -1.333333333x + x2 = 0 + 60 Combine like terms: 0 + 60 = 60 -1.333333333x + x2 = 60 The x term is -1.333333333x. Take half its coefficient (-0.6666666665). Square it (0.4444444442) and add it to both sides. Add '0.4444444442' to each side of the equation. -1.333333333x + 0.4444444442 + x2 = 60 + 0.4444444442 Reorder the terms: 0.4444444442 + -1.333333333x + x2 = 60 + 0.4444444442 Combine like terms: 60 + 0.4444444442 = 60.4444444442 0.4444444442 + -1.333333333x + x2 = 60.4444444442 Factor a perfect square on the left side: (x + -0.6666666665)(x + -0.6666666665) = 60.4444444442 Calculate the square root of the right side: 7.774602526 Break this problem into two subproblems by setting (x + -0.6666666665) equal to 7.774602526 and -7.774602526.Subproblem 1
x + -0.6666666665 = 7.774602526 Simplifying x + -0.6666666665 = 7.774602526 Reorder the terms: -0.6666666665 + x = 7.774602526 Solving -0.6666666665 + x = 7.774602526 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '0.6666666665' to each side of the equation. -0.6666666665 + 0.6666666665 + x = 7.774602526 + 0.6666666665 Combine like terms: -0.6666666665 + 0.6666666665 = 0.0000000000 0.0000000000 + x = 7.774602526 + 0.6666666665 x = 7.774602526 + 0.6666666665 Combine like terms: 7.774602526 + 0.6666666665 = 8.4412691925 x = 8.4412691925 Simplifying x = 8.4412691925Subproblem 2
x + -0.6666666665 = -7.774602526 Simplifying x + -0.6666666665 = -7.774602526 Reorder the terms: -0.6666666665 + x = -7.774602526 Solving -0.6666666665 + x = -7.774602526 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '0.6666666665' to each side of the equation. -0.6666666665 + 0.6666666665 + x = -7.774602526 + 0.6666666665 Combine like terms: -0.6666666665 + 0.6666666665 = 0.0000000000 0.0000000000 + x = -7.774602526 + 0.6666666665 x = -7.774602526 + 0.6666666665 Combine like terms: -7.774602526 + 0.6666666665 = -7.1079358595 x = -7.1079358595 Simplifying x = -7.1079358595Solution
The solution to the problem is based on the solutions from the subproblems. x = {8.4412691925, -7.1079358595}
| X+(X*.1)=40.85 | | 3x+84=15 | | 3/8n=5/6 | | 2(7s+3)-8s=2(3s+4)-12 | | 3x+13+25=2+7x | | 56-6=8 | | 3x-2/2x+1=-2 | | -9(2w-9)=0 | | K^2+5k+8=2 | | 50y=200 | | 18x-4x=9-3x | | 4(4-a)-2(a-4)=-10a-2a | | 4x-(30-x)+25=80 | | 15+4x+60=11x+12 | | 30+you=7 | | 2*(24/2y)*y=48 | | 5u(8u-1)=0 | | 4y=14-2x | | -1=-4+b | | (x^69-i^69)(x^69+i^69)=0 | | dy/dx=1/(2x-y^2) | | 7(x+2)=2x+57 | | 108=4z | | y=1/(2x-y^2) | | 0.5=1-e^-((t-1)/10) | | 4(4-a)-2(a-4)=-10-2a | | -2(5v-3)+3v=3(v+4) | | 7x+19+2x+15=133 | | -4h+6=-6h-8 | | 21b=14+b | | -17=m+71 | | 126=3p |